2013
DOI: 10.4238/2013.december.19.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endovascular abdominal aortic aneurysm repair in nonagenarians

Abstract: ABSTRACT. The aim of this study was to investigate the safety and efficacy of endovascular abdominal aortic aneurysm repair (EVAR) in nonagenarians. From May 2003 to March 2011, 12 nonagenarian abdominal aortic aneurysm patients were treated with endovascular repair including two emergencies. The mean age of patients was 92.5 ± 1.6 years (range: 90-95 years), and 11 of the patients (91.7%) were men. Technical success, perioperative complications, and mortality were evaluated. The follow-up protocol consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Of the 40 studies selected for further analysis 10,1757 none were randomized controlled trials. There were 26 cohort studies, 4 case-control studies, and 10 case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 40 studies selected for further analysis 10,1757 none were randomized controlled trials. There were 26 cohort studies, 4 case-control studies, and 10 case series.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining reported on differences between general anesthesia and loco-regional anesthesia. 20,21,29,34…”
Section: Resultsmentioning
confidence: 99%
“…Our usual practice is nonoperative management in this patient group. However, selective use of EVAR in octogenarians and nonagenarians has been shown to have acceptable success, [11][12][13] and given that our patient's AAA had expanded by >1 cm in <1 year to 6.8 cm, we offered EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Others nonagenarian's studies have reported similar results. 19,21,22 Shan et al 25 reported that Quality of Life on patients >80 years after EVAR, takes longer to recover compared with younger patients, and physical health domains recover more slowly than mental health domains. Pol et al 6 showed that recovery in QOL and the domains of mobility, self-care, and usual activities are delayed longer than expected on patients >80 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Others nonagenarian’s studies have reported similar results. 19,21,22 Table 1 summarizes studies of nonagenarians undergoing EVAR.…”
Section: Discussionmentioning
confidence: 99%